Management of Scabies Cases with Secondary Infection in Children through Family Medicine Approach - Jeffry Luwito; Dewi Indah Lestari; Christabella Putri Yulius; Melvira Putri Liviansyah (Science Midwifery, 2022)
Scabies is a skin infestation caused by Sarcoptes scabiei (var. hominis). The prevalence of scabies in Indonesia is 4.60% - 12.95% and ranks the third most common disease. The Cikupa Public Health Center experienced an increase in the number of new scabies cases as many as 34 new cases in January - June 2022 compared to June - December 2021 as many as 21 new cases. Female patient aged 5 years and 10 months suffered from scabies with secondary infection and had transmitted it to other family members. Problem analysis was carried out by mapping the Mandala of Health with the principles of family medicine and comprehensive management. Ms. K and her family members recovered from scabies and no new lesions appeared. The patient and her families have been given education about scabies and there are no new infections in them so further transmission of scabies can be prevented. The family medicine approach and Mandala of Health have helped Ms. K and her family in the treatment and eradication of scabies.